2012
DOI: 10.1155/2012/834598
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Transfer of Antibiotic Resistance from an Environmental Plasmid to Foodborne Pathogens

Abstract: Pathogens resistant to multiple antibiotics are rapidly emerging, entailing important consequences for human health. This study investigated if the broad-host-range multiresistance plasmid pB10, isolated from a wastewater treatment plant, harbouring amoxicillin, streptomycin, sulfonamide, and tetracycline resistance genes, was transferable to the foodborne pathogensSalmonellaspp. orE. coliO157:H7 and how this transfer alters the phenotype of the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…According to Ramsden et al (2010), class 1 integrons appeared to be ubiquitous among tetracycline-resistant bacterial isolates. Van Meervenne et al (2012) observed that an environmental plasmid can be transferred to foodborne pathogenic bacteria at high transfer ratios. In our study, the frequency of conjugation ranged from 2.0 × 10 −6 to 6.5 × 10 −5 per donor strain.…”
Section: Culture-based Approachmentioning
confidence: 99%
“…According to Ramsden et al (2010), class 1 integrons appeared to be ubiquitous among tetracycline-resistant bacterial isolates. Van Meervenne et al (2012) observed that an environmental plasmid can be transferred to foodborne pathogenic bacteria at high transfer ratios. In our study, the frequency of conjugation ranged from 2.0 × 10 −6 to 6.5 × 10 −5 per donor strain.…”
Section: Culture-based Approachmentioning
confidence: 99%
“…ARGs are often carried on broad host range mobile genetic elements (MGEs) (Byrne-Bailey et al 2011;Akiyama et al 2010;Binh et al 2008), which are of particular concern because these vectors may be disseminated from environmental hotspots through water and food webs into clinically relevant pathogenic or opportunistic bacteria (Van Meervenne et al 2012;Jayaraman 2009). Benveniste and Davies (1973) first suggested a link between environmental and clinical AR after detecting high similarities between gentamicin-resistant enzymes from soil-associated Actinomycetes and enzymes that confer the same resistance in human pathogens such Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia, and Staphylococcus aureus.…”
Section: Persistence Of Pharmaceuticals In Effluents and Twwirrigatedmentioning
confidence: 99%
“…Plasmid pB10 was previously tagged with mini-Tn5-P A1-04/03 ::gfp, a Tn5 derivative transposon encoding green fluorescent protein (GFP) to produce pB10::gfp (24). The persistence of pB10::gfp was determined in Pseudomonas putida H2 (15), P. putida UWC-1 (25), and P. veronii S34 (26).…”
Section: Methodsmentioning
confidence: 99%